2015
DOI: 10.1021/acs.jpca.5b07298
|View full text |Cite
|
Sign up to set email alerts
|

DCl Transport through Dodecyl Sulfate Films on Salty Glycerol: Effects of Seawater Ions on Gas Entry

Abstract: Gas-liquid scattering experiments were employed to measure the entry and dissociation of the acidic gas DCl into salty glycerol coated with dodecyl sulfate ions (DS(-) = CH3(CH2)11OSO3(-)). Five sets of salty solutions were examined: 0.25 and 0.5 M NaCl, 0.25 M MgCl2, 0.25 M CaCl2, and artificial sea salt. DS(-) bulk concentrations were varied from 0 to 11 mM, generating DS(-) surface coverages of up to 34% of a compact monolayer, as determined by surface tension and argon scattering measurements. DS(-) surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 65 publications
(130 reference statements)
4
21
0
Order By: Relevance
“…20 Furthermore, Shaloski et al have recently shown that the surface activity of anionic surfactants is enhanced in the presence of Ca 2+ compared to that for Na + . 21 For monovalent cations, K + was depleted in the aerosol phase relative to Na + (EF Na + K + = 0.72 ± 0.05) across the full aerosol size range, which agrees well with previous work reporting stronger binding affinities of Na + with COO − compared to those of K + . 22 The trend in the calculated values in size-resolved aerosol shows depletion of chloride (Cl − ) relative to Na + in the aerosol size ranges where LC enrichment is greatest (Figure 3b).…”
supporting
confidence: 91%
“…20 Furthermore, Shaloski et al have recently shown that the surface activity of anionic surfactants is enhanced in the presence of Ca 2+ compared to that for Na + . 21 For monovalent cations, K + was depleted in the aerosol phase relative to Na + (EF Na + K + = 0.72 ± 0.05) across the full aerosol size range, which agrees well with previous work reporting stronger binding affinities of Na + with COO − compared to those of K + . 22 The trend in the calculated values in size-resolved aerosol shows depletion of chloride (Cl − ) relative to Na + in the aerosol size ranges where LC enrichment is greatest (Figure 3b).…”
supporting
confidence: 91%
“…Organic surface concentration and packing resulting from ionic interactions, and the subsequent impact on gas phase uptake is illustrated in segment A. 28 Segment B shows results that N 2 O 5 uptake is not suppressed in the presence of complex organics produced over the course of a microbial bloom. 31 Segment C illustrates a previously unrecognized reaction pathway for HNO 3 with functional groups present in bioorganic molecules produced during microbial blooms.…”
Section: Accounts Of Chemical Researchmentioning
confidence: 99%
“…Thus, simple systems informed by results from complex systems have been utilized to establish model chemical systems that can be leveraged to provide parametrizations of SSA chemistry that improve the understanding of real world complexity in the future. These include using standard scales derived from reference chemical systems against which to compare gas entry through organic surface active species, 28 organic species detected in complex SSA to inform molecular-scale simulations to produce thermodynamic models that can use surface tension values to predict the morphology of liquid−liquid phase separated organic-containing aerosol, 41 and model SSA compounds to better predict CCN activation of distinct SSA particle types. 36 …”
Section: Accounts Of Chemical Researchmentioning
confidence: 99%
“…[17] Investigations into the role of ions in SSA indicate that cations such as Mg 2þ and Ca 2þ can enhance organic species at the interface, which has implications for the surface packing of organic molecules and subsequent interfacial reactivity. [18,19] Further, various chemical properties (e.g. surface activity, solubility, interfacial molecular structure) have been observed to play a role in defining the transfer of chemical matter from the ocean to SSA.…”
Section: Introductionmentioning
confidence: 99%